Transform the industrial landscape into an iconic park at Tanjung Agas, Tangkak, Johor Darul Takzim/ Mohammad Fazleezan Ahmad Yusof - Ahmad Yusof, Mohammad Fazleezan (2017)
Public open space in Malaysian context is a planned and managed space for current and future generations for the purpose of public protection and pleasure of unique values. It played an important role in order to improve the quality of life in urban area and supporting the urban inhabitants. The essential of identifying the identity and character of the habitations with connecting them in wide green network which provide public benefits, environmental and biodiversity. Same situation with the study area which located at Tanjung Agas, Tangkak, Johor, the significance of the study the idea in reducing the strong image of southern gateway of Tangkak district as industrial hub by proposing new public open space on the study area. The aim of this study is to create a public space that will contribute toward a healthy lifestyle, meet the human need and environmental benefits. The objectives of this study which focus on to determine the landscape character of southern gate of T angkak by enhancing the character of the site and resolve the accessibility issues through sustainable landscape approach, to provide design master plan that portrays Muar and Tangkak recreational spaces for public user and to enhance the balance between human needs and environmental benefits public open spaces. The need of recreational area for local community, Kampung Tanjung Agas and the opportunities on the reserved green area provided along the Muar River. The inventory and analysis process has been conducted and it is focused on the distinctiveness of the historical significance collected on the study area and its surrounding elements based on referred research methodology by using placemaking design process by Project for Public Space. The data collected are synthesized to identify the potential area to be enhanced and the final phase of this study will provide a design proposal which is important to forecast the guideline planning and design practice in this study. The design proposal were named as Gerbang Muara Park which is reflect the identity of Muar and Tangkak that help to overcome strong image of industrial hub and create conducive environment between local community and industrial activities. By creating public spaces, the existence of the park will contribute toward healthy lifestyle, meet the human need and environmental benefits.